Schistosome Infection and Schistosome-Derived Products as Modulators for the Prevention and Alleviation of Immunological Disorders - Mu, Yi; McManus, Donald P.; Hou, Nan; Cai, Pengfei (Frontiers in Immunology, 2021)
Abstract: Parasitic helminths, comprising the flatworms (tapeworms and flukes) and nematodes (roundworms), have plagued humans persistently over a considerable period of time. It is now known that the degree of exposure to these and other pathogens inversely correlates with the incidence of both T helper 1 (Th1)-mediated autoimmunity and Th2-mediated allergy. Accordingly, there has been recent increased interest in utilizing active helminth worm infections and helminth-derived products for the treatment of human autoimmune and inflammatory diseases and to alleviate disease severity. Indeed, there is an accumulating list of novel helminth derived molecules, including proteins, peptides, and microRNAs, that have been shown to exhibit therapeutic potential in a variety of disease models. Here we consider the blood-dwelling schistosome flukes, which have evolved subtle immune regulatory mechanisms that promote parasite survival but at the same time minimize host tissue immunopathology. We review and discuss the recent advances in using schistosome infection and schistosome-derived products as therapeutics to treat or mitigate human immune-related disorders, including allergic asthma, arthritis, colitis, diabetes, sepsis, cystitis, and cancer.